2013
DOI: 10.1007/s10815-013-9966-4
|View full text |Cite
|
Sign up to set email alerts
|

Failure of GnRH agonist-triggered oocyte maturation: its cause and management

Abstract: In cases where GnRHa fails to trigger oocyte maturation, a rescue protocol entailing re-triggering with HCG can produce successful outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 11 publications
0
22
0
1
Order By: Relevance
“…The incidence of EFS after the use of a GnRHa trigger in our population was 1.8% (6/322). This incidence varies based on the available studies (Griesinger et al, 2011;Honnma et al, 2011;Asada et al, 2013;Kummer et al, 2013) (Table III). Castillo et al (2012) reported the highest incidence (3.5%) based on a population of young, healthy oocyte donors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The incidence of EFS after the use of a GnRHa trigger in our population was 1.8% (6/322). This incidence varies based on the available studies (Griesinger et al, 2011;Honnma et al, 2011;Asada et al, 2013;Kummer et al, 2013) (Table III). Castillo et al (2012) reported the highest incidence (3.5%) based on a population of young, healthy oocyte donors.…”
Section: Discussionmentioning
confidence: 99%
“…When this is added to the data currently available (Asada et al, 2013;Kummer et al, 2013) in the literature, mature oocytes were collected with the use of rescue hCG in patients with EFS after a GnRH trigger in 92.3% of reported cases (12/13). All 6 patients responded during the phase of controlled ovarian stimulation with Ն 18 follicles Ͼ 11 mm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bu öneriler; GnRHa trigger sonrası OPU günü tek overe OPU yapılması ve eğer oosit yoksa ya da çok az ise serum progesteron seviyesine bakılması, sonrasında ise serum progesteron seviyesi yüksek değilse hCG ile ikinci bir tetiklemeyi takiben ikinci OPU'nun bilateral overlere yapılması, son olarak da OPU'da toplanan bütün oositlerin daha sonra transfer edilmek üzere dondurulması şeklindedir. 40 …”
Section: Gnrha Teti̇kleme Sonrasi Yüksek Doz öStradi̇ol Ve Progesteron unclassified